Why Adults Participate in Learning Activities in Jordan Guidelines for Recruitment - Nimer, Kamal ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
Knowledge of Jordan's historical background and the role of well-educated individuals and groups in motivating adults to participate in learning activities is essential for finding ways to recruit and retain adults in education programs. Some means that have proven effective include the following: (1) persuading religious and social leaders to exert their influence in getting adults to come to literacy classes; (2) door-to-door canvassing; (3) organized trips to historical sites in Jordan as an inducement to recruiting and retaining students; (4) providing adult students with an identification card that can be used to obtain low-cost medical care; (5) forming adult committees for dealing with religious, social, educational, and nursery school affairs; (6) using religious committees to recruit adults; (7) having women visit other women and tell them about educated Muslim women; (8) guest speakers lecturing about the value of education; (9) holding annual exhibitions to display the work of adult literacy students; and (10) hiring highly qualified teachers to teach and deal with adult learners. These and other techniques have proved to be effective in recruiting and retaining adult students in Jordan. (KC)
ERIC Note: Paper presented at the Annual Conference of the American Association for Adult and Continuing Education (Atlantic City, NJ, October 1989).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Basic Education; Adult Literacy; Adult Students; Developing Nations; Dropout Prevention; Educational History; Foreign Countries; Guidelines; Incentives; Literacy Education; Participation; School Holding Power; Student Recruitment; Womens Education; Jordan; Speeches/Meeting Papers; Reports, Descriptive